THE EFFECTS OF COGNITION AND FUNCTIONAL PERFORMANCE ON CORE STABILITY IN THE ELDERLY POPULATION: A CROSS-SECTIONAL STUDY - Liepa, Agris; Gudiņa, Undine; Dubinina, Evita; Larins, Viesturs; Kaupuzs, Aivars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The researches indicate that core stability may play a substantial role in reducing fall risk in the elders. Nevertheless, cognition and functional performance has been identified with fall risks as well. The impact of functional performance elements and/or cognition on core stability, to complement the intervention programs for seniors in the future, has not been fully studied. This study aimed to assess the effects of leg strength, static balance, walking speed and cognition on the core stability scores. In a cross-sectional design study a sample of 62 participants were eligible for the study.  Elderly aged 60 or older living in Social care centers or autonomous were recruited. Independent variables included static balance, walking speed, leg strength measured by Short Physical Performance Battery, cognition (alertness, divided attention, selective attention, and working memory) evaluated with the Rehacom screening software and age. Dependent variable core stability (the ability to maintain appropriate contraction of muscle transversus abdominis) was assessed performing Prone test with Chattanooga Stabilizer Pressure Biofeedback. A hierarchical multiple regression was used for statistical analysis. Static balance and cognition presented greater effects significantly explaining 18% and 13% of the variability of core stability, whereas no significant effects of walking speed and leg strength were found on core stability. Exercise programs where static balance and cognition tasks are implemented to complement core stability performance might be worth investigating and compare with other intervention methods to reduce the risk of falling in the elderly population.